Stratification processes in Uzbek society: General and specific - Kholbekov, Abdugani; Berdiev, Babur (Linguistics and Culture Review, 2021)
The stratification processes taking place in the newly independent states of the post-Soviet space have both common starting principles and special tendencies. Under the conditions of market reforms, stratification processes are deepening. Based on a comparative analysis of various approaches, the author identified nine types of stratification systems and their general historical nature. A summary description of the specifics of each of them is provided. As a special feature, the article shows the division of Uzbek society into various social strata and strata according to their status indicators.